Clinical endocrinology - Whitehead, Saffron (Scion, 2013)
Clinical Endocrinology unites a sound knowledge of basic science principles with a case-based approach to clinical management of patients with endocrinopathy, and is suitable for not only undergraduate medical and biomedical science students, but also those pursuing specialist study modules.